2017
DOI: 10.1002/pbc.26816
|View full text |Cite
|
Sign up to set email alerts
|

Salvage rates and prognostic factors after relapse in children and adolescents with malignant peripheral nerve sheath tumors

Abstract: Our study confirmed the unsatisfactory prognosis for pediatric patients with relapsing MPNST and pointed to a risk-adapted stratification model for the purposes of deciding second-line treatments. For the time being, an aggressive surgical approach seems to be the only effective salvage treatment and should be recommended. New therapeutic approaches are under evaluation with a view to improving current outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Actually, 5-year OS rate was more than 50% in studies [15,[24][25][26] in which the participants were more than 300. For an Italian study focusing on pediatric patients (n=73) with relapsing MPNST, Bergamaschi, L. et al [28] reported that the survival rate was 15.8% at 5 years which was the lowest rate in our included studies. For non-NF 1 MPNST children (n=44) in the Netherlands, Martin, E. et al [42] showed the highest 5-year survival rate (75.8%) in these cohorts.…”
Section: -Year Os Rate 5-year Efs and Lr Ratementioning
confidence: 59%
See 1 more Smart Citation
“…Actually, 5-year OS rate was more than 50% in studies [15,[24][25][26] in which the participants were more than 300. For an Italian study focusing on pediatric patients (n=73) with relapsing MPNST, Bergamaschi, L. et al [28] reported that the survival rate was 15.8% at 5 years which was the lowest rate in our included studies. For non-NF 1 MPNST children (n=44) in the Netherlands, Martin, E. et al [42] showed the highest 5-year survival rate (75.8%) in these cohorts.…”
Section: -Year Os Rate 5-year Efs and Lr Ratementioning
confidence: 59%
“…Among sarcomas, MPNST has the highest recurrence rate [44]. Bergamaschi, L. et al [28] reported the highest LR rate of 86.3% in 73 patients, with 64.4% only local recurrence and 21.9% local and metastatic recurrence of MPNST. Keizman, D. et al [37] investigated 46 patients with MPNST, indicating 13% of patients occurred local recurrence with follow-up ranging from 3 to 120 months.…”
Section: -Year Os Rate 5-year Efs and Lr Ratementioning
confidence: 99%
“…One possible reason why the survival rates of AYA patients with MPNST were poorer than those of the other age groups is that a larger part of AYA patients with MPNST may have neurofibromatosis type 1 (NF1). MPNST patients with NF1 have been reported to be significantly younger at the time of MPNST diagnosis than those with sporadic tumors (median age, 26 years vs. 53 years) and have poor outcomes [16,17]. Thus, the mean age of MPNST patients with NF1 is within the AYA age group.…”
Section: Discussionmentioning
confidence: 99%
“…The picture, therefore, remains bleak for MPNST, and while Bergamaschi and colleagues demonstrate the ability to rescue some patients who relapse, this is limited to tiny numbers of patients . The message from these tumors is therefore “get it right first time around.” This is possible, but only if the patient presents early with a small tumor or, indeed, if current and future programs in screening NF1 patients with DNLs lead to the removal of these early premalignant lesions.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] They conclude that this is possible, albeit in small numbers, in particular if a radical second operation is performed leading to an R0 resection. 1 Perhaps, however, this paper deflects attention from a more important message that pediatric MPNSTs continue to have an extremely poor outcome unless they are small, localized, and resectable. 4,6 Indeed, the median overall survival in the pediatric age group is 30 months, which decreases in the older adolescent group to 23 months.…”
mentioning
confidence: 99%